Color Vision Deficiency in Pakistan Railways Employees - Aneeq Ullah Baig Mirza, Yasir Iqbal, Aqsa Malik, Sohail Zia (Pakistan Journal of Ophthalmology, 2016)
Purpose: To determine the frequency of color vision deficiency (CVD) in Pakistan Railways employees Study Design: Cross sectional descriptive study. Place and Duration of the Study: Outdoor patient department of Ophthalmology, Pakistan Railways Hospital, Rawalpindi over a period of one year from 1 Feb 2015 to 30 Jan 2016. Material and Methods: Prospective Data was collected by using convenient non probability sampling technique of Pakistan railways employees presenting for the annual vision checkup. Slit lamp was used to evaluate the anterior and posterior segments whereas visual acuity was measured on the Snellen’s chart after refraction. Color vision was assessed binocularly using the Ishihara isochromatic color plates (38 plates) with the best correction in a trial frame. The type of color vision deficiency was labeled from the Ishihara chart key. The patients with best corrected visual acuity 6/9 after refraction and no history of medication or surgery were included in the study .The patients who had visual acuity <6/9, medication history of anti tuberculosis, central nervous system acting drugs or ocular surgical history were excluded from the study.